Economic Integation Agreements, Border Effects, and Distance Elasticities in the Gravity Equation - Jeffrey H. Bergstrand; Mario Larch; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using a novel common econometric specification, we examine the measurement of three important effects in international trade that historically have been addressed largely separately: the (partial) effects on trade of economic integration agreements, national borders, and bilateral distance. First, recent studies focusing on precise and unbiased estimates of effects of economic integration agreements (EIAs) on members' trade may be biased upward owing to inadequate control for exogenous unobservable country-pair-specific technological innovations (decreasing the costs of international relative to intranational trade); we find evidence of this bias using a properly specified gravity equation. Second, our novel methodology yields economically plausible and statistically significant estimates of the declining effect of national borders on world trade, now accounting for endogenous EIA formations and unobserved country-pair heterogeneity in initial levels. Third, we confirm recent evidence providing a solution to the distance-elasticity puzzle, but show that these estimates of the declining effect of distance on international trade are biased upward by not accounting for endogenous EIA formations and unobserved country-pair heterogeneity. We show that these results are robust to a battery of sensitivity analyses allowing for phase-ins of agreements, lagged terms-of-trade effects, reverse causality, various estimation techniques, disaggregation, inclusion of intranational trade, and accounting for firm-heterogeneity and country-selection bias.
Keywords: F13; F14; F15; 330; international trade; economic integration agreements; gravity equations